The Perfect Storm of Education Reform: High-Stakes Testing and Teacher Evaluation - Croft, Sheryl J. (Social justice, 2015)
This article examines seemingly disconnected education reform policies and posits that their unprecedented alignment is eroding the bedrock of public education. U sing Georgia as an example, the authors demonstrate how neoliberal efforts to reform education occur through three systematic and interconnected fronts: political climate change, the testing industrial complex, and a mesoscale evaluation system. The authors challenge assertions that those reforms increase academic achievement and global competitiveness. Instead, the orchestrated alignment is being experienced as an assault on the supposed beneficiaries (i.e., public education and teacher education). These conceptual weather fronts can serve as a means to analyze stated intentions versus outcomes of education policy. The authors conclude with grassroots responses by students, teachers, and others to the destructive elements of reform.